Comparative transcriptome analysis revealed resistance differences of Cavendish bananas to Fusarium oxysporum f.sp. cubense race1 and race4 - Dong, Honghong (BMC Genet, 2020)
BACKGROUND: Banana Fusarium wilt is a devastating disease of bananas caused by Fusarium oxysporum f. sp. cubense (Foc) and is a serious threat to the global banana industry. Knowledge of the pathogenic molecular mechanism and interaction between the host and Foc is limited. RESULTS: In this study, we confirmed the changes of gene expression and pathways in the Cavendish banana variety ‘Brazilian’ during early infection with Foc1 and Foc4 by comparative transcriptomics analysis. 1862 and 226 differentially expressed genes (DEGs) were identified in ‘Brazilian’ roots at 48 h after inoculation with Foc1 and Foc4, respectively. After Foc1 infection, lignin and flavonoid synthesis pathways were enriched. Glucosinolates, alkaloid-like compounds and terpenoids were accumulated. Numerous hormonal- and receptor-like kinase (RLK) related genes were differentially expressed. However, after Foc4 infection, the changes in these pathways and gene expression were almost unaffected or weakly affected. Furthermore, the DEGs involved in biological stress-related pathways also significantly differed after infection within two Foc races. The DEGs participating in phenylpropanoid metabolism and cell wall modification were also differentially expressed. By measuring the expression patterns of genes associated with disease defense, we found that five genes that can cause hypersensitive cell death were up-regulated after Foc1 infection. Therefore, the immune responses of the plant may occur at this stage of infection. CONCLUSION: Results of this study contribute to the elucidation of the interaction between banana plants and Foc and to the development of measures to prevent banana Fusarium wilt. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s12863-020-00926-3.